The Effectiveness of e-Booklet on Female Sex Workers’ Knowledge and Behaviour of HIV/AIDS Prevention in Semarang - Nabilla Angel Sukma Wati; Nila Titis Asrining Tyas (Lembaga Pengembangan Kinerja Dosen, 2025)
Sex workers (FSW) are a key population at high risk of HIV/AIDS because they work frequently serving guests. HIV prevention knowledge and behavior are not optimal, education using the e-booklet